Education as the Foundation of Knowledge in Education Management: the Concept of Education and Comparison of its Application in Indonesia and Malaysia - Rhoni Rodin; Endang Endang; Irwan Fathurrochman; Lukman Asha; Jumira Warlizasusi (International Journal on Advanced Science, Education, and Religion, 2024)
This article examines the foundational role of education in shaping the field of education management, focusing on its historical development, theoretical perspectives, and practical applications in Indonesia and Malaysia. It traces the evolution of educational thought and management practices, highlighting key schools of thought that have influenced education systems in both countries. By comparing the implementation of education management principles in Indonesia and Malaysia, the study provides insights into the similarities and differences in their educational approaches and policy adaptations. The findings aim to contribute to a deeper understanding of how educational foundations support effective management practices and the ways in which cultural and institutional contexts influence education management. This comparative analysis is expected to benefit policymakers, educators, and researchers interested in developing and enhancing education management systems.